Dinamika Struktur Kemukjizatan Al-Qur`an - Muhamad Ali Mustofa Kamal (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2015)
This study seeks to unravel the question of quranic miracles as a dynamic aspect. By using a qualitative approach, the efforts for re-structuring of miracles aspectsof the Koran into `I'jâz in the text and beyond the text resulted in essence of quranic miracles as proof of the truth of prophetic treatise. The structure of the quranic miracles constantly evolving dynamic in line with the growing public acceptance dimension following the age dimension. The dynamics of the miracle of the Qur`an forms evolved following the development of the rationality of the Muslims in every age. The classical era, `i'jâz Qur`an more confronted with theissue of linguistic (bayân) which focuses on grammar (naẓm), rhetoric and balagha of Koran. In its development, elaboration of the aspects `i’jâz rules of the Koran into major and minor becomes an important issue to find a common thread I’jâz study the Koran and socio-cultural discourse in analyzing aspects of the reception of the Koran in Islamic societies as evidentiary support and response tothe challenges (tahaddi) against aspects of the miracle of the Qur`an.